Compression Strain-Induced Folding at Intersecting Deformation Macrobands on the Copper Single Crystals; AIP Conference Proceedings; Vol. 1909 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2017 (AMHS’17) - Chumaevskii A. V. (2017, 2017)
Title screen